Decolorization of different textile dyes by Penicillium simplicissimum and toxicity evaluation after fungal treatment - Bergsten-Torralba,L.R. (2009)
The objective of this study was to investigate the capacity of decolorization and detoxification of the textile dyes Reactive Red 198 (RR198), Reactive Blue 214 (RB214), Reactive Blue 21 (RB21) and the mixture of the three dyes (MXD) by Penicillium simplicissimum INCQS 40211. The dye RB21, a phthalocyanine, was totally decolorized in 2 days, and the others, the monoazo RR198, the diazo RB214 and MXD were decolorized after 7 days by P. simplicissimum. Initially the dye decolorization involved dye adsorption by the biomass followed by degradation. The acute toxicity after fungal treatment was monitored with the microcrustacean Daphnia pulex and measured through Effective Concentration 50% (EC50). P. simplicissimum reduced efficiently the toxicity of RB21 from moderately acutely toxic to minor acutely toxic and it also reduced the toxicity of RB214 and MXD, which remained minor acutely toxic. Nevertheless, the fungus increased the toxicity of RR198 despite of the reduction of MXD toxicity, which included this dye. Thus, P. simplicissimum INCQS 40211 was efficient to decolorize different textile dyes and the mixture of them with a significant reduction of their toxicity. In addition this investigation also demonstrated the need of toxicological assays associated to decolorization experiments.